Букварь: [0+] / Ирина Гурина - Гурина Ирина Валерьевна (Первый учебник малыша, 2019)
Экземпляры: ф.28 (20190705) / Инвентарный номер: 063099 / Цена: 41.00 / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6